Fostering integrity among school principals’ ethical leadership: a comprehensive systematic review - ak Bujang, Mackencidy; Alias, Bity Salwana; Mansor, Azlin Norhaini (Institute of Advanced Engineering and Science, 2025)
This systematic review explores the importance of promoting integrity in the ethical leadership of school principals, particularly when ethical lapses by educational leaders can impact outcomes. Increasing societal pressures and a complex educational environment highlight the importance of ethical leadership in shaping the school environment and student success. However, the lack of a complete understanding of how to effectively create ethical leadership remains a major concern. An extensive search of scholarly articles was conducted from reputable databases such as Scopus, Web of Science, and ERIC, focusing on studies published between 2020 and 2024. The flow of study based on PRISMA framework. The database found (n=19) final primary data was analyzed. The finding was divided into three themes which is academic integrity and ethics in education, leadership and integrity in educational management, and character and value education in schools. Comprehensive programs and administrative support are essential to fostering integrity in schools, while effective leadership plays an important role in shaping a conducive school environment. In conclusion, the need to foster integrity among school principals across disciplinary boundaries requires concerted efforts and innovative approaches to prepare ethical leaders to navigate the complexities of the contemporary educational landscape and inspire positive change.